2019
DOI: 10.3390/foods8100458
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oxidative Status of Human Milk, Human Milk Fortifiers and Preterm Infant Formulas

Abstract: Preterm and low birth weight infants require specific nutrition to overcome the accumulated growth deficit, and to prevent morbidities related to postnatal growth failure. In order to guarantee an adequate nutrient-intake, mother’s own milk, when available, or donor human milk, are usually fortified with additional nutrients, in particular proteins. Fortification with processed ingredients may result in additional intake in oxidative compounds, deriving from extensive heat treatments, that are applied during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…To ensure a continuous human milk-based diet with sufficient nutrition for their preterm infants, mothers often need to express their milk, fortify and refrigerate it ( 30 ). Even though changes in the chemical properties of breastmilk following fortification have been reported previously ( 37 39 ), fortification of breastmilk is extremely important for nutrition and growth of some preterm infants ( 40 ). Compared to preterm breastmilk, our data demonstrate that the volatile profile of breastmilk with bovine milk-based fortifier (BMF) is marked by products generated through lipolysis (fatty acids) and lipid auto-oxidation (ketones and aldehydes), suggesting that changes in breastmilk properties occur within the recommended refrigerated storage period for fortified breastmilk ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure a continuous human milk-based diet with sufficient nutrition for their preterm infants, mothers often need to express their milk, fortify and refrigerate it ( 30 ). Even though changes in the chemical properties of breastmilk following fortification have been reported previously ( 37 39 ), fortification of breastmilk is extremely important for nutrition and growth of some preterm infants ( 40 ). Compared to preterm breastmilk, our data demonstrate that the volatile profile of breastmilk with bovine milk-based fortifier (BMF) is marked by products generated through lipolysis (fatty acids) and lipid auto-oxidation (ketones and aldehydes), suggesting that changes in breastmilk properties occur within the recommended refrigerated storage period for fortified breastmilk ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because of the immature renal tubular reabsorption of AAs, an excessive protein intake could be responsible for an increased excretion of these compounds in urine [ 38 ]. Even though we did not characterize the AA composition of the two fortifiers, considering the similarity of the two groups under investigation in terms of immaturity characteristics (i.e., gestational and postnatal age) and protein and energy intakes, as well as the differences in form and type of proteins between the two fortifications [ 39 ], we do not rule out a possible role of AA compositions and of protein quality on the higher urinary levels of leucine and lysine observed in B-HMF as compared with D-HMF. Furthermore, very recently, a clinical trial [ 40 ] on term infants breastfed or fed with two different formulas demonstrated that, before the introduction of complementary foods, circulating AAs, including leucine and lysine, were more abundant in the serum metabolome of formula-fed infants, whose metabolic phenotype was also characterized by high levels of insulin and urea.…”
Section: Discussionmentioning
confidence: 99%
“…The authors tested the antioxidant potential of human milk with ABTS and TBARS tests and obtained results indicating a high pro-health potential as necessary for healthy growth at every stage of an infant’s life, but also stressed that this milk loses its value during the pasteurization process. On the other hand, Pozzo et al [ 65 ] also discuss the health potential of human milk but mentioned that its antioxidant potential, tested with ABTS and DPPH methods, was lower than infant formulas dedicated to preterm and low birth weight infants. It was stated that the use of human milk minimizes the intake of dietary oxidative compounds in comparison to infant formulas due to the malondialdehyde content.…”
Section: Discussionmentioning
confidence: 99%